Pairwise Multiple Comparison Adjustment Procedure for Survival Functions with Right-Censored Data - Colak, Ertugrul (Comput Math Methods Med, 2017)
The aim of this study is to propose a new pairwise multiple comparison adjustment procedure based on Genz's numerical computation of probabilities from a multivariate normal distribution. This method is applied to the results of two-sample log-rank and weighted log-rank statistics where the survival data contained right-censored observations. We conducted Monte Carlo simulation studies not only to evaluate the familywise error rate and power of the proposed procedure but also to compare the procedure with conventional methods. The proposed method is also applied to the data set consisting of 815 patients on a liver transplant waiting list from 1990 to 1999. It was found that the proposed method can control the type I error rate, and it yielded similar power as Tukey's and high power with respect to the other adjustment procedures. In addition to having a straightforward formula, it is easy to implement.